2015
DOI: 10.1080/21645515.2015.1008873
|View full text |Cite
|
Sign up to set email alerts
|

24 year outcomes of hepatitis B vaccination in Hangzhou, China

Abstract: To evaluate the impact of the universal infant HepB vaccination program on hepatitis B virus infection in Hangzhou, China. Hepatitis B incidences and HepB vaccination rates of Hangzhou from 1990 to 2003 were acquired from the historical paper-documents, while which were derived from China Information System for Diseases Control and , P < 0.001). Significant association was found between incidence of hepatitis B and HepB vaccination rate (r D 0 .946, x 2 D 11.813, P for trend D 0.001). A total of 5605 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…This may explain the findings of Essam et al in Saudi Arabia where despite effective vaccine coverage, the rate of infections with HBV increased with age and most infections occurring in persons aged >14 years of age [19] and in Europe in which Nardone et al found that despite Universal HBV vaccination programmes established seroprevalence of HBsAb was lower than the reported vaccine coverage in three countries [20]. And in China where Jian et al evaluated the impact of the universal infant Hepatitis B vaccination program on hepatitis B virus infection in Hangzhou, China and found among participants aged 0-59years a prevalence of HBsAg and HBsAb of 6.19%, and 45.83% respectively [21]. He et al found a significant reduction in the level of HBsAb among children 1-2 years after when compared to 3-15years [22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may explain the findings of Essam et al in Saudi Arabia where despite effective vaccine coverage, the rate of infections with HBV increased with age and most infections occurring in persons aged >14 years of age [19] and in Europe in which Nardone et al found that despite Universal HBV vaccination programmes established seroprevalence of HBsAb was lower than the reported vaccine coverage in three countries [20]. And in China where Jian et al evaluated the impact of the universal infant Hepatitis B vaccination program on hepatitis B virus infection in Hangzhou, China and found among participants aged 0-59years a prevalence of HBsAg and HBsAb of 6.19%, and 45.83% respectively [21]. He et al found a significant reduction in the level of HBsAb among children 1-2 years after when compared to 3-15years [22].…”
Section: Resultsmentioning
confidence: 99%
“…Lee, Chuanfang [23] postulated that the protection afforded by vaccination is long lasting even after antibody levels fall below 10 mIU/ml [23]. However, other studies has shown HBV prevalence despite the WHO established coverage and have recommended revaccination or booster doses [13][14][15][16][17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, aged respondents in our study might be beyond the required age for free HB immunization by the MoH. On the other hand, aged respondents might take more care of the health of children than themselves [6,9]. In accordance with the study of Yan et al, our findings showed that the more highly educated respondents had a higher vaccination rate and were more willing to be vaccinated if they had not been vaccinated before [27].…”
Section: Discussionmentioning
confidence: 99%
“…HB vaccination has been proved to be the most efficient and economical way to prevent HBV infection and spread [6]. Previous study highlighted that HB vaccine could provide long-term protection against risks of infection encountered in later life [7].…”
Section: Introductionmentioning
confidence: 99%